Labour market integration, human capital formation, and mobility - Alexander Haupt; Silke Übelmesser (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
In this paper, we analyse the implications of labour market integration in a two-region model with local human capital externalities and congestion effects. We show that integration can be a double-edged sword. Integration and the ensuing agglomeration of skilled labour can reduce "real" income in both regions. Even if there is a "winning" region, human capital and real income in the two regions together might decline (but need not). However, integration can increase total real income even if it depresses human capital formation. We further explore how the degree of labour mobility and the strength of the congestion effects shape the impact of integration on human capital and income.
Keywords: F22; R23; J24; R12; 330; agglomeration; Human capital; labour market integration; migration